Evaluation of Mechanical and Microstructural Properties of Waste Tire Improved Cemented Clay - Lutf Al-Subari; Abdullah Ekinci (Journal of Natural Fibers)
Each year, an enormous number of tires approach the end of their useful lives, posing threats to human health and the environment. On the other hand, cement is frequently used to treat soils in geotechnical applications, while its production causes a significant environmental impact. Thus, this study provides a disposal alternative by investigating the influence of tire rubber fiber (TRF) as a partial replacement of cement in artificially cemented soils. Unconfined compressive strength (qu) and ultrasonic pulse velocity (UPV) were measured on the various mixtures to assess strength, stiffness, and ductility index. Statistical analysis and regression models were conducted, and a novel approach to estimate rubberized-cemented-clay was proposed to determine Go, qu, and E from a single nondestructive test. Moreover, SEM was performed to observe the interaction of the TRF and cement with the clay on a microscopic scale. The results showed that the 2.5% TRF content improves rubberized cemented clay’s strength, stiffness, and ductility index by around 12–15%. Furthermore, up to 10% of the TRF blends achieved the minimum requirements for rammed earth, base, and sub-base treated soils. However, 20% of TRF reduces Go, and qu, by around 20–30% while improving the ductility index by 35–40%.